2020
DOI: 10.19053/01228420.v17.n2.2020.10979
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de la luz sobre la germinación de semillas champa (Campomanesia lineatifolia R. & P.)

Abstract: La champa (Campomanesia lineatifolia R. & P.) es una especie frutal de la familia Myrtaceae, con gran potencial de comercialización por el agradable sabor de sus frutos. Su propagación por semillas presenta dificultades asociadas a un bajo porcentaje de germinación y un tiempo prolongado para culminar esta etapa. Como se desconoce el efecto que pueda generar la luz en las semillas de champa, el objetivo de este estudio fue determinar el efecto de diferentes tratamientos de luz sobre la germinación de semil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…The results of the morphological variables exhibited statistical differences based on the type of light and its intensity. In terms of red light, our findings align with those of Porras Mechán et al (2020), who observed that seeds treated with red light displayed higher germination percentage, compared to those treated with blue light, as noted in Campomanesia lineatifolia. Similarly, Paniagua-Pardo et al (2015) reported a 25 % increase in germination rates 68.5 ± 1.12 ab 66.0 ± 1.58 bc Significant differences p<0.05 (*), highly significant differences p<0.01 (**).…”
Section: Discussionsupporting
confidence: 90%
“…The results of the morphological variables exhibited statistical differences based on the type of light and its intensity. In terms of red light, our findings align with those of Porras Mechán et al (2020), who observed that seeds treated with red light displayed higher germination percentage, compared to those treated with blue light, as noted in Campomanesia lineatifolia. Similarly, Paniagua-Pardo et al (2015) reported a 25 % increase in germination rates 68.5 ± 1.12 ab 66.0 ± 1.58 bc Significant differences p<0.05 (*), highly significant differences p<0.01 (**).…”
Section: Discussionsupporting
confidence: 90%
“…According to Silva and Fonseca (2016), this genus is characterized by its citrus-flavored fruits. It is an exotic fruit native to the Amazon rainforest that has considerable potential for commercialization and is currently being introduced in different markets in Colombia (Balaguera et al, 2009;Balaguera-López and Herrera, 2012a;Porras et al, 2020). This fruit has a high concentration of organic acids, sugars and volatile compounds (Balaguera and Herrera, 2012a), which makes it highly desirable for consumption, fresh or in processed products (Álvarez-Herrera et al, 2009a).…”
mentioning
confidence: 99%